Enzyme profile of insecticide-resistant phenotypes of Aedes aegypti from Bagua, Peru - Cordova Paz Soldan, Ofelia Magdalena (2023)
Temephos and deltamethrin insecticides have been widely used to control Aedes aegypti in Bagua Grande district, Utcubamba, Amazonas, Peru. For this reason, the enzyme profile related to temephos and deltamethrin resistance in A. aegypti from Bagua Grande were evaluated. To determine the resistance status, bioassays were conducted with temephos using larvae and with deltamethrin using adults. Enzymes profile were evaluated by biochemical assays of αEST, βEST, GSTs, and remaining AChE in survived individuals to selective doses of both insecticides. Esterase patterns of larvae and adults were observed by native-PAGE. The population showed temephos susceptibility, with RR 50 = 3.06 and 83.95% mortality, and deltamethrin resistance with a mortality equal to 1.21%. Enzyme assays revealed highly altered levels of GST and AChE in larvae and altered levels of αEST and highly altered levels of GST and AChE in adults. Native-PAGE only showed common bands to susceptible strain. Results suggest that the presence of GST and AChE do not improve temephos resistance, while αEST, GST and AChE mechanisms are involved in deltamethrin resistance in A. aegypti from Bagua Grande.